Kendala Guru dalam Melaksanakan Penilaian Autentik pada Masa Pandemi Covid-19 di Sekolah Dasar - Dwi Afrilia (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
This article is motivated by changes that have occurred in the learning process due to the Covid-19 pandemic. This article talks about the analysis of the application of authentic assessment during the Covid-19 pandemic at SD Negeri 050591 Padang Cermin. In the implementation of authentic assessment, a teacher still experiences many obstacles, especially in the preparation of instruments. Plus the state of the learning process is currently carried out online or online. The purpose of this study is the obstacles experienced by teachers in carrying out authentic assessments during the Covid-19 pandemic in elementary schools. This type of research is qualitative descriptive. Data collection techniques used were observation, interviews, and documentation. The focus of this research is how to apply authentic assessment during the Covid-19 pandemic where learning is currently being carried out online, how teachers carry out authentic assessments if learning is done online and the obstacles experienced by teachers in implementing authentic assessments during the Covid-19 pandemic . The results of this study are that there are several problems experienced by students, teachers, and parents in online teaching and learning activities such as less mastery of technology, additional internet quota costs, additional work for parents in accompanying their children to learn, communication. and decreased socialization between students, teachers and parents has reduced interaction and unlimited working hours for teachers because they have to communicate and coordinate with parents, other teachers, and school principals at all times. The COVID-19 pandemic affects many things including educational life , parents of students, students and the learning process, as a teacher who has the responsibility to educate students can not stop. Teachers must find suitable ways to promote the learning process academically and socio-emotional. Teachers must be able to manage classrooms in classrooms and online classes.